Acculturative Stress and Leisure among Chinese International Graduate Students. (2nd November 2018) - Zhou, Yilun; Zhang, Hongping; Stodolska, Monika
ABSTRACT: This study explored the roles of leisure participation in helping Chinese international graduate students cope with acculturative stress. In particular, it examined (a) the expectations and preparations with respect to acculturative stress made by the students prior to their arrival to the United States, (b) the acculturative stressors experienced by the students during the postarrival transition phase, (c) the role of leisure participation in coping with acculturative stress, and (d) the limitations of leisure as a coping strategy and the negative impacts of leisure on acculturative stress. Two rounds of semi-structured interviews were conducted with 15 first-year Chinese international graduate students attending a large midwestern university. The findings revealed that due to the unique cultural influence and the status of international students, the participants experienced distinctive acculturative stressors. Although leisure participation was an effective tool in combating acculturative stress, in some circumstances it a led to a plethora of negative outcomes.